Esophageal hiatus surgery. Videolaparoscopic approach. - Rodríguez, Gustavo; Fernández, Gonzalo; Gatti, Adriana; Balboa, Oscar (Cirugía del Uruguay, 2003)
Since the early nineties, surgery of esophageal hiatus (treatment of disease due to gastroesophageal reflux, gastric denervative surgery in treatment of duodenal chronic ulcer) through videolaparoscopic approach, has gained broad dissemination and acceptance at world leve!.